Increasing Participation of Non-State Actors in ASEAN: Problems and Options - Ludiro Madu; Hestutomo Restu Kuncoro (Intermestic: Journal of International Studies, 2022)
This article aims to assess ASEAN's commitment to enhancing the role of non-state actors that has emerged since the late 1990s. There is a tendency that grassroots social movement activists do not seem to have an official forum in ASEAN. Although some non-state actors have gained access to ASEAN, this privilege is largely granted to business interest groups and elite think-tanks. This research applied qualitative method by using the concept of historical institutionalization, this paper seeks to explain the characteristics of an institution using events that occurred in the past during the process of creating and consolidating institutions. The concept is also responsive to explaining ---and, in some cases, even prescribing--- changes. The study found that the increased participation of non-state actors will increase ASEAN's legitimacy in carrying out its growing role in the region. This article contributes to offer some options that ASEAN must cultivate to improve participation of non-state actors. Keywords: ASEAN, historical institutionalism, non-state actors, participatory regionalism